2018
DOI: 10.1159/000490021
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-223 Suppresses Osteoblast Differentiation by Inhibiting DHRS3

Abstract: Background/Aims: In this study, we aimed to use bioinformatics tools to identify the specific miRNAs and mRNAs involved in osteogenic differentiation and to further explore the way in which miRNA regulates osteogenic differentiation. Methods: The microarray GSE80614, which includes data from 3 human mesenchymal stromal cells (hMSCs) and 3 hMSCs after 72 hours (hr) of osteogenic differentiation, was used to screen for differentially expressed mRNAs. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…The findings revealed that miR-338-3p showed an opposite trend of expression in BMSCs with age and exerted negative functions on PCSK5, thereby limiting bone formation. Several studies also reported that an increasing number of miRNAs could regulate BMSC differentiation (31)(32)(33). In the present study, increased expression of miR-338-3p was observed in BMSCs of older rat samples, which indicated a counter-productive role of miR-338-3p in osteogenesis.…”
Section: Discussionsupporting
confidence: 71%
“…The findings revealed that miR-338-3p showed an opposite trend of expression in BMSCs with age and exerted negative functions on PCSK5, thereby limiting bone formation. Several studies also reported that an increasing number of miRNAs could regulate BMSC differentiation (31)(32)(33). In the present study, increased expression of miR-338-3p was observed in BMSCs of older rat samples, which indicated a counter-productive role of miR-338-3p in osteogenesis.…”
Section: Discussionsupporting
confidence: 71%
“…MiR-223 was recently identified as a key modulator of osteoblastic differentiation in MC3T3-E1 cells, which targets histone deacetylase 2 (HDAC2). 55 To summarize, the obtained ZrO 2 ALD coatings are cytocompatible toward the MC3T3 osteoblastic cell line. The coatings promote the metabolic potential and may mitigate the effect of miR-21 inhibition, increasing expression of osteogenic markers, both at mRNA and miRNA level.…”
Section: Aldmentioning
confidence: 85%
“…Several miRNAs modulate osteogenic differentiation; thus they have been dubbed as osteomiRs. For instance, miR-125b regulates osteoblastic differentiation of human MSCs through targeting of BMPR1b [20], whereas miR-223 suppresses osteoblast differentiation by inhibiting DHRS3 [21]. However, miRNAs functions during differentiation of hAM-MSCs to osteogenic lineage have not been completely explored.…”
Section: Discussionmentioning
confidence: 99%